Legal status of certain preparations with herbal extracts in the European Community - Stoicescu, Iuliana; Popescu, Antoanela; Suciu, Felicia; Radu, Marius Daniel; Bușuricu, Florica; Lupu, Carmen Elena (Technium BioChemMed, 2023)
This study focuses on the legislative regulation of cosmetic products containing plant extracts in Romania and Europe. The classification of such products as medicinal products, cosmetics, or food supplements is explored within the context of European and Romanian laws. Cosmetic products with herbal extracts must meet the safety, quality, and efficacy requirements outlined in Regulation (EC) No 1223/2009 of the European Parliament and the Council. The distinction between cosmetic products and other categories like medicinal products, medical devices, or biocidal products is emphasized, with clear definitions provided to differentiate them. A “cosmetic product” is defined as any substance or mixture intended for external application on specific body parts or oral cavity areas, serving purposes like cleaning, perfuming, appearance alteration, protection, maintenance, or odor correction. The study finds that there are numerous cosmetic preparations with herbal extracts available in the Romanian and European markets, all registered as cosmetic products in the Cosmetics Notification Portal. The assessment of whether a product falls under the cosmetic category depends on an evaluation of its characteristics on case-by-case basis. The paper also explores the diverse range of cosmetic products with herbal extracts, including skin creams, gels, make-up, hygiene, hair care, and sunbathing products among others. The study concludes that clear legislative regulations play a crucial role in ensuring the safety and quality of cosmetic products containing herbal extracts within the European and Romanian markets.